Pelatihan Peningkatan Kapasitas Guru Bahasa Inggris dalam Memanfaatkan Chat GPT/AI untuk Mendukung Proses Pembelajaran - Siti Ngaisah; Ekka Zahra Puspita Dewi; Salma Hira; Febri Wulandari; Nabila Fateha (Jurnal Madani Mengabdi (JMM), 2025)
A big challenge for teachers nowadays is how to teach students to critical thinking in making an essay or scientific work originally from their idea not using an application like Chat GPT/AI is so difficult. In this research, the researcher asks all of the English teachers in Islamic senior high schools to gather  MGMP Bahasa Inggris Blitar Raya to discuss about this, the result of this research is that the researcher found some perspectives about using Chat GPT/AI for students, there are positive and negative effect from it. Some English teachers need the ability to make students critically thinking in every single task without using Chat GPT/AI, so the researcher gave some tips and tricks to face this problem. Based on the results, before entering the classroom the teachers ask all of the students to collect their gadgets on the teacher’s table and the teacher must provide students with clear assignments and finish them at that time, so there was no time to find the answer by using the gadget. In the conlcusion, as a teacher, we need some management in a digital era.